MENINGKATKAN HASIL BELAJAR SUMBER-SUMBER ENERGI PADA PEMBELAJARAN IPA MELALUI STRATEGI CARD SORT SISWA KELAS II MADRASAH IBTIDAIYAH NEGERI PEMBANTANAN SUNGAI TABUK KABUPATEN BANJAR - Rahman, Gazali (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2015)
This research aims to improve student learning outcomes in class IIB second semester at MIN Pembantanan, Sungai Tabuk, Banjar Regency. It is for Learning science using active learning model with card sort type. This study used a qualitative descriptive method. Classroom action research study was conducted in two cycles. At each cycle of the first cycle and the second cycle consists of two meetings with the allocation of time on each cycle of 2x35 minutes. This research subject is class IIB MIN Pembantanan, Sungai Tabuk, Banjar Regency, second semester of academic year 2013/2014, the number of students as many as 18 people with 10 men and 8 women. Collecting data in this study were obtained through observation and written tests, while data analysis technique used is the average and percentage. Results of this study was obtained (1) Activities of teachers in the implementation of learning with the learning strategy card sort in science on material “energy sources” in Class IIB MIN Pembantanan, Sungai Tabuk, Banjar district is well and maximum. The quality of learning is increasing based on teacher’s activity in in teaching process; it increased with the percentage of 75% to 95.8%. Overall average percentage of the learning process of teachers included in both categories at all; (2) Activity of students in the percentage increased from 68% to 92%; (3) The results of student learning increased with the implementation of learning strategy card sort on material “energy source”, it is seen from the test results of students in the first cycle of the average value of 67.7 in the first meeting and the second meeting of the 90, then in the second cycle at the first meeting 78.8 and in the second meeting 90.5 or 91. Thus it can be said to be successful because of the results achieved already meet the target of completeness in learning which mastery learning value of 60.00